2015
DOI: 10.3310/hta19230
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial and cost-effectiveness analysis of high-frequency oscillatory ventilation against conventional artificial ventilation for adults with acute respiratory distress syndrome. The OSCAR (OSCillation in ARDS) study

Abstract: BackgroundPatients with the acute respiratory distress syndrome (ARDS) require artificial ventilation but this treatment may produce secondary lung damage. High-frequency oscillatory ventilation (HFOV) may reduce this damage.ObjectivesTo determine the clinical benefit and cost-effectiveness of HFOV in patients with ARDS compared with standard mechanical ventilation.DesignA parallel, randomised, unblinded clinical trial.SettingUK intensive care units.ParticipantsMechanically ventilated patients with a partial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 102 publications
(112 reference statements)
1
34
0
Order By: Relevance
“…However, we did find it difficult to achieve high rates of long-term follow-up data collection, in keeping with previous intensive care trials, 54,55 and a considerable amount of staff resource was involved in delivering this aspect of the trial. It is important to identify barriers to follow-up in these patients to inform future critical care studies.…”
Section: Economic Evaluationsupporting
confidence: 62%
See 2 more Smart Citations
“…However, we did find it difficult to achieve high rates of long-term follow-up data collection, in keeping with previous intensive care trials, 54,55 and a considerable amount of staff resource was involved in delivering this aspect of the trial. It is important to identify barriers to follow-up in these patients to inform future critical care studies.…”
Section: Economic Evaluationsupporting
confidence: 62%
“…The cost-utility analysis included only patients with complete cost and QALY data but, of those alive at 12 months, only 45% completed both the 6-and 12-month follow-up questionnaires and some data were missing from these completed questionnaires. Previous intensive care trials 54,55 have also found it difficult to achieve high rates of long-term data collection and the experience of the HARP-2 trial confirms that this is a difficult population to follow up. Furthermore, economic data are particularly likely to be missing owing to the reliance on multiple components within HRQoL and resource use questionnaires required for the calculation of QALYs and costs.…”
Section: Figure 14mentioning
confidence: 96%
See 1 more Smart Citation
“…The mean time horizon for the withintrial component of the economic evaluations in the remaining 18 studies was 8 months (median 9 months and range 1 to 12 months). Some studies extrapolated outcomes beyond the trial follow-up period using decision analytic modelling methods [25,26,28] with up to 60 months [25] and lifetime [15,16,28,29] extrapolations beyond the study follow-up periods. Most economic evaluations were conducted from the perspective of the UK National Health Service (NHS) (n=4) or the NHS/Personal Social services (n=9) in accordance with NICE guidance for appraising health technologies [30].…”
Section: Summary Of Rcts Included In the Reviewmentioning
confidence: 99%
“…For the purpose of this review, we measured the baseline (or first) time point for describing healthrelated quality of life as reported by individual studies; conventionally in trial-based economic evaluations this is taken as the time of randomisation. Nine (47%) of the 19 studies used the EQ-5D to measure health-related quality of life of patients, 5 (26%) used the EQ-5D in combination with another instrument (primarily the SF-12/36 [26,33,35], HUI-3 [32] and the paediatric PedsQL [36]), 1 (5%) [18] used the 15D instrument [34] and another 1 (5%) used the HUI-3 [28]. The remaining 3 (17%) studies [29] [25,27] did not report a primary health-related quality of life data collection process.…”
Section: Measurement Of Health-related Quality Of Lifementioning
confidence: 99%